Visual Attention Modulates Phenomenal Consciousness: Evidence From a Change Detection Study - Simione, Luca; Di Pace, Enrico; Chiarella, Salvatore G.; Raffone, Antonino (Frontiers in Psychology, 2019)
The distinction between phenomenal and access consciousness has been influential in the field of consciousness studies. Both Block and Lamme proposed that access consciousness, or narrow cognitive accessibility, is related to a limited capacity working memory, and that phenomenal consciousness, or broad cognitive accessibility, is related to iconic memory or, more recently, to a fragile (intermediate) short-term memory store with a larger capacity than working memory. They have also highlighted the preattentive nature of phenomenal consciousness, and of the related iconic and fragile visual short-term stores, thus selectively linking attention with access consciousness, in line with Baars and Dehaene, among others. However, a range of electrophysiological and neurophysiological studies suggest that visual attention can affect early responses of neurons in visual cortex, before conscious access. Furthermore, some theories and neurocomputational models suggest earlier attentional biases related to phenomenal consciousness. To solve this controversy, and to shed light on the relationships of attention with iconic memory and subsequent stages of visual maintenance, we conducted an experiment with a novel procedure of change detection based on delayed cueing of the target for report with high- and low-priority objects marked by colour. In line with our hypothesis, the results show an attentional bias toward high-priority objects in the memory array with the longer (600 and 1200ms) cueing delays associated with a fragile (intermediate) visual short-term memory, but not with the shorter cueing delays (16.6 and 200ms) associated with iconic memory. These findings therefore suggest two stages of phenomenal consciousness before access consciousness: a first preattentive stage related to iconic memory, and a second stage related to fragile visual short-term memory intermediate between iconic and visual working memory, which is modulated by visual attention in a time-dependent manner. Finally, our results suggest the dissociation between a mid-level visual attention modulating phenomenal consciousness and a central attention directing access consciousness.